Little red shed - Young, Adam; Young, Jennifer (Breakwater Books, 2020)
Once upon a fine morning, a little shed awakens to discover she isn't quite the same as she used to be. Uncertain and feeling as if she no longer fits in, she decides to leave home and sets out to sea. All alone on the wide, wide ocean, she meets an extraordinary new friend who sees how special she really is, and with newfound confidence, the little red shed returns home and inspires everyone to cherish their differences
Keywords: Sheds / Juvenile fiction; Self-confidence / Juvenile fiction; Self-confidence; Sheds; Selbstvertrauen; Hütte; Bilderbuch